2014
DOI: 10.1590/0004-2730000003283
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related Hashimoto’s thyroiditis – A new variant of a well known disease

Abstract: SUMMARYHashimoto's thyroiditis (HT) has been characterized for many years as a well-defined clinicopathologic entity, but is now considered a heterogeneous disease. IgG4-related HT is a new subtype characterized by thyroid inflammation rich in IgG4-positive plasma cells and marked fibrosis. It may be part of the systemic IgG4-related disease. We report a case of a 56-year-old Portuguese man who presented with a one-month history of progressive neck swelling and dysphagia. Laboratory testing revealed increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
3
2
0
1
Order By: Relevance
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details. 10,11 The cytological features in our case corroborate the histological findings. The prominent microfollicular distribution with Hurthle cell change may result in a false diagnosis of Hurthle cell neoplasm, as illustrated in our case.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details. 10,11 The cytological features in our case corroborate the histological findings. The prominent microfollicular distribution with Hurthle cell change may result in a false diagnosis of Hurthle cell neoplasm, as illustrated in our case.…”
Section: Discussionsupporting
confidence: 85%
“…The cytological findings of IgG4 thyroiditis are poorly documented, with rare reports in the literature describing features of lymphocytic thyroiditis, without additional details . The cytological features in our case corroborate the histological findings.…”
Section: Discussionsupporting
confidence: 78%
“…Our patient's symptoms due to mass effect (dysphagia, airway obstruction) rather than chemical insult (eg, heat or cold intolerance, tremors, changes in energy level, etc.) align with reports of Luiz et al, 14 Kang et al, 16 and Zhao et al 18 in which neck swelling without symptoms of thyroid dysfunction were observed. Indeed, Li et al 1 found 39% (11/28) of IgG4-RHT cases to be associated with subclinical hypothyroidism.…”
Section: Clinical Featuressupporting
confidence: 92%
“…IgG4-related Hashimoto's thyroiditis, characterized by thyroid inflammation rich in IgG4+ plasma cells and marked fibrosis, has been identified. [ 9 ] Because the current patient refused to undergo a thyroid biopsy, it was uncertain whether there was a IgG4+ plasma cell infiltrate in the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%